Market Consequences of Earnings Management in Response to Security Regulations in China* - HAW, IN‐MU; QI, DAQING; WU, DONGHUI; WU, WOODY (Contemporary Accounting Research, 2005)
Abstract Under the 1996‐98 security regulations in China, the accounting rate of return on equity (ROE) has to be greater than 10 percent for three "consecutive" years for a firm to qualify for stock rights offers. Despite declining economic conditions during this period, the percentage of firms reporting ROE between 10 and 11 percent is about "three" times that for 1994‐95. This unique regulatory environment provides a natural experimental setting for the empirical assessment of earnings‐management behavior and its consequences. This study examines whether listed Chinese firms manage earnings to meet regulatory benchmarks and whether regulators and investors consider the quality of earnings in their respective regulatory and investment decisions. On the basis of a sample of listed Chinese firms from 1996 to 1998, we observe that managers execute transactions involving below‐the‐line items and use income‐increasing accounting accruals to meet regulatory ROE targets for stock rights offerings. The firms that apply for, but fail to receive, regulatory approval manage earnings more significantly than do firms that receive approval and pair‐matched control firms. Our market study also suggests that investors differentiate the quality of earnings and put less value on earnings suspected of a greater degree of management. Overall, our results imply that the regulatory bodies and investors to some extent make rational adjustments for the quality of earnings.